Enhancing the Performance of Grid-Tied Renewable Power Systems Using an Optimized PI Controller for STATCOM - Aljohani, Masnour (International Journal of Robotics and Control Systems, 2025)
Integrating electrical networks with renewable energy sources in hybrid systems may effectively meet increasing power demands while reducing reliance on traditional energy sources. Wind gusts in wind energy conversion systems (WECSs), along with variations in temperature and irradiance in photovoltaic (PV) systems, render these systems vulnerable. Three-phase faults at the point of common coupling (PCC) can disconnect renewable energy sources (RESs) from the grid, threatening system stability. This study enhances a hybrid PV-WECS system through the implementation of a static synchronous compensator (STATCOM) to mitigate wind gust effects and maintain RES connectivity during three-phase faults at the point of common coupling (PCC). STATCOM manages reactive power exchange between renewable energy sources and the grid through two PI controllers. The gains of the PI controller are optimized through elephant herding optimization (EHO), demonstrating superior performance compared to particle swarm optimization (PSO) in terms of PCC voltage stability and system efficiency. In three-phase faults, the EHO demonstrates superior performance over the PSO, achieving a PCC voltage of 0.7 in contrast to 0.37, thereby maintaining voltage levels within acceptable limits in the connecting zone according to grid codes. The EHO-optimized PI controllers for the STATCOM successfully reduce the SRG current during this fault, decreasing it from 155 (with PSO) to 111 (with EHO). Under wind gust conditions, the power profile obtained from the SRG is markedly enhanced when employing EHO in comparison to PSO.